Association of Interstitial Lung Disease With Clinical Characteristics of Chinese Patients With Systemic Lupus Erythematosus - Yaling CHEN,; Yanqing WANG,; Xiangfang CHEN,; Huishun LIANG,; Xuwei YANG, (Archives of Rheumatology, 2020)
Objectives: This study aims to evaluate the frequency and clinical and laboratory features of interstitial lung disease (ILD) in Chinese patients with systemic lupus erythematosus (SLE) and to evaluate the association of ILD with the clinical features. Patients and methods: The study included 505 SLE patients (64 males, 441 females; mean age 35.3±15.3 years; range, 14 to 87 years) who were categorized into two groups as 449 patients without ILD and 56 patients with ILD based on evidence obtained from high-resolution computed tomography images. The demographic data, clinical and laboratory findings, SLE disease activity index score, and Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index of all patients were also recorded and statistically analyzed. Results: The ILD frequency in patients with SLE was 11.1%. Compared to the group of SLE patients without ILD, the group of SLE patients with ILD possessed the following statistical differences: elderly age, longer illness duration, lower level of anti-double-stranded deoxyribonucleic acid, and higher level of serum complement 3, increased ratios of Raynaud’s phenomenon, moist rales and tachypnea. Multivariate logistic regression results suggested that elderly age (≥60 years), long illness duration (1-10 years, ≥10 years), Raynaud’s phenomenon, and tachypnea were statistically associated with the occurrence of ILD in SLE patients. Conclusion: Chinese SLE patients who possessed the factors that were statistically associated with ILD, namely, elderly age (≥60 years old), long illness duration (≥1 years), Raynaud’s phenomenon, and tachypnea, were recommended to be monitored for the possibility of ILD.